Palladium‐Catalyzed Intramolecular Reductive Cross‐Coupling of Csp2Csp3 Bond Formation. Issue 27 (28th May 2014) - Liu, Hui; Wei, Jianpeng; Qiao, Zongjun; Fu, Yana; Jiang, Xuefeng
Abstract A Pd‐catalyzed efficient reductive cross‐coupling reaction without metallic reductant to construct a Csp2Csp3 bond has been reported. A PdIV complex was proposed to be a key intermediate, which subsequently went through double oxidative addition and double reductive elimination to produce the cross‐coupling products by involving Pd0/II/IV in one transformation. The oxidative addition from PdII to PdIV was partially demonstrated to be a radical process by self‐oxidation of substrate without additional oxidants. Furthermore, the solvent was proved to be the reductant for this transformation through XPS analysis.